P002 A Summary of the Methods That the Alexandria Centre for Evidence-Based Clinical Practice Guidelines (CEBCPGs) uses to produce Clinical Practice Guidelines for the Healthcare Quality Directorate of Alexandria University Hospitals and Healthcare Sectors in Alexandria. (15th August 2013) - Amer, Y; Elzalabany, M; Omar, T; Ibrahim, A
Abstract : Background: The CEBCPGs produces CPGs on high priority health topics to establish recommendations based on best evidence. The authors summarise the main methods used in adaptation and implementation of these CPGs. Objectives: The aim of this work was to promote simplicity, avoid redundancy and decrease delay in the process of CPG adaptation. Methods: Part 1) Cross-sectional/ or retrospective study and assessment of the current situation of practice in selected healthcare settings to identify/select high priority health topic(s) and to justify the need for producing a CPG for this topic(s) and expected benefit and outcome for its implementation; Part 2) consists of the Methodology for CPGs adaptation, based on an adaptation of The ADAPTE Process developed by the ADAPTE Collaboration. Results: Three main ADAPTE steps were identified as cornerstones of the process and another two steps in the assessment module were replaced by the AGREE Domains scores. Implications for Guideline Developers/Adapters/Users: 1. Health Topics for CPG Adaptation & Implementation should be selected based on Cross-sectional study/surveys for local Healthcare Professionals. 2. Adaptation of CPGs as a valid alternative to de novo development has many benefits for resource utilisation and unifying practice. 3. The ADAPTE process is that it is adaptable to local context and resources. 3. Successful CPGs Implementation Strategies; i)For Practitioners: Implementation tools designed to facilitate behavioural/practice changes (e.g. Posters & Brochures of Clinical algorithms & Flow charts), Educational material, Educational meetings (e.g. conferences, lectures & workshops) and Local Clinical Champions; ii) For Patients/Carers: Education materials and meetings.